Pengaruh Kombinasi Mirror Therapy dan Ball Grip terhadap Kekuatan Otot Ekstremitas Atas pada Pasien Stroke - Handika Bayu Cahyono; Indah Wahyu Ningsih; Retno Setyowati (Journal of Medical Practice and Research, 2026)
Stroke is one of the leading causes of disability in Indonesia, with a prevalence of 10.9 per 1,000 population. This condition often results in weakness in the upper extremity muscles, which limits daily activities and reduces the patient's quality of life. Rehabilitation efforts to overcome this condition can be done through a combination of mirror therapy and ball grip as non-pharmacological therapies that play a role in increasing muscle strength through neuroplasticity and motor stimulation mechanisms. This study aims to determine the effect of a combination of mirror therapy and ball grip on increasing upper limb muscle strength in stroke patients at RSI Sultan Agung Semarang. This study used a pre-experimental design with a one-group pretest-posttest design. A sample of 26 respondents was selected using purposive sampling with the inclusion criteria of stroke patients in the physical rehabilitation stage and having muscle strength of 1–3. The intervention was given for 10–15 minutes five times a week for four days. Muscle strength was measured using Manual Muscle Testing (MMT) on a scale of 0–5 before and after the intervention. The results of the analysis showed a significant increase in upper extremity muscle strength after the intervention (p < 0.05), with the average MMT score increasing from 13.0 to 15.5. This combination of therapies is effective, safe, and easy to implement.